SciDev.Net (SciDev.Net, 2016)
"SciDev.Net's website is the world’s leading source of reliable and authoritative news, views and analysis on information about science and technology for global development [...] Our mission is to help individuals and organisations apply evidence and insights from science and technology to decision-making in order to have a positive impact on equitable and sustainable development and poverty reduction." --- Includes constantly updated news and feature articles, topic-based dossiers with news, policy briefs, and links to other sites, regional gateways on Africa, Asia, Latin America and the Middle East, and opinion articles. Also includes selected articles from Science and Nature
Gesehen am 20.05.2016
Keywords: Website